Satureja khuzistanica Essential Oil-Loaded Solid Lipid Nanoparticles Modified With Chitosan-Folate: Evaluation of Encapsulation Efficiency, Cytotoxic and Pro-apoptotic Properties - Tabatabaeain, Seyedeh Farnoosh; Karimi, Ehsan; Hashemi, Mehrdad (Frontiers in Chemistry, 2022)
The study aimed to synthesize Satureja khuzistanica essential oil-loaded SLN nanoparticles and to modify the surface of nanoparticles with folate-bound chitosan (SEO-SCF-NPs), and finally to investigate the effects of its toxicity and pro-apoptosis. For this purpose, the SEO-SLN nanoparticles were prepared using stearic acid, lecithin, tween 80, and water by high-pressure homogenization method. After characterization by FTIR, SEM, DLS, and ZETA potential methods, its toxicity effect against normal (HFF) and cancer (MCF-7) cells were evaluated by MTT assay. The occurrence of apoptosis in MCF-7 cells was assessed by flow cytometry and molecular analysis. The obtained results revealed the formation of round nanoparticles with a size of 279.40 nm, single dispersed (PDI: 0.3) and stable (ζ –potential: +31.69 mV). SEO-SCF-NPs indicated the effect of selective toxicity against MCF-7 cells (IC50: 88µg/mL). Molecular analysis showed that SEO-SCF-NPs could inhibit cancer cells by activating the internal pathway of apoptosis as well as cell cycle disruption. Our finding suggests that SEO-SCF-NPs is a suitable candidate for preclinical cancer studies.